A Wiener-Hopf analysis of the coaxial waveguide radiator - Tayyar, Ismail Hakki; Büyükaksoy, Alinur (My University, 2011)
In the present work, by formulating the radiation from a semi-infinite coaxial waveguide in a different manner that described in [1], we obtained a single modified Wiener-Hopf equation whose solution involves three sets of infinitely many expansion coefficients satisfying three infinite systems of linear algebraic equations. These systems are then solved numerically and some graphical results showing the effects of the radii of the inner and outer cylinder on the radiation phenomenon are presented. © 2011 IEEE. © 2011 Elsevier B.V., All rights reserved.
2011 13th International Conference on Electromagnetics in Advanced Applications, ICEAA'11 -- Torino -- 87148
Keywords: Coaxial waveguides; Expansion coefficients; Infinite system; Wiener-Hopf analysis; Wiener-Hopf equation; Electromagnetism; Integral equations; Linear equations; Radiation effects; Waveguide components; Circular waveguides